OKRES BUDŻETOWY W UJĘCIU POZNAŃSKIEJ SZKOŁY SKARBOWOŚCI - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 2012)
Twórcą poznańskiej szkoły skarbowości w 1919 r. na Wydziale Prawno-Ekonomicznym Uniwersytetu Poznańskiego był prof. Edward Taylor, mentor naukowy i moralny wielu tysięcy polskich prawników oraz ekonomistów. Po II wojnie światowej aktywność naukowa Katedry Prawa Finansowego Uniwersytetu Poznańskiego przez 50 lat koncentrowała się – z przyczyn politycznych – głównie na prawie budżetowym. Ośrodek poznański był w tym okresie czołowym ośrodkiem naukowym w Polsce zajmującym się finansami państwa i finansami lokalnymi. W opracowaniu omówiono niektóre prace naukowe pracowników Katedry Prawa Finansowego UP, w których podjęto pionierskie wówczas aspekty okresu budżetowego i wieloletniego planowania finansowego.

*Poznan´ School of Public Finance was created in 1919 by professor Edward Taylor, a member of the Law and Economy Faculty of the Poznan´ University, and a mentor and moral role model for thousands of Polish lawyers and economists that followed. For political reasons, for fifty years after World War II, the research work of the Department of Financial Law of the University’s Law and Economy Faculty concentrated on budget laws. In that period Poznan´ became a leading research centre specialising in state and local finance in Poland. The paper presents selected dissertations of the researchers from the Department of Financial Law, devoted to the pioneering aspects of the budget period and long-term financial planning.
A BUDGET PERIOD IN THE APPROACH OF POZNAN´ SCHOOL OF PUBLIC FINANCE
Keywords: Poznańska szkoła skarbowości; prawo budżetowe; okres budżetowy; Poznań School of Public Finance; budget law; budget period